2022
DOI: 10.7759/cureus.21970
|View full text |Cite
|
Sign up to set email alerts
|

Advancements in the Treatment of Triple-Negative Breast Cancer: A Narrative Review of the Literature

Abstract: Triple-negative breast cancers (TNBCs) are aggressive tumors that are more common in young women, African American populations, and those with hereditary mutations. These tumors are notable for their high recurrence rate and predilection for chemoresistance. The goal of this narrative review is to describe the current treatment options for patients diagnosed with TNBC and to review the studies that have put forward these recommendations. We searched PubMed and Cochrane databases for free full-text, English-lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 66 publications
(120 reference statements)
0
17
0
Order By: Relevance
“…While TNBC accounts for only 15-20% of breast cancers, this intrinsic subtype is particularly aggressive, more likely to metastasize, and due in part to the lack of targeted therapies, results in worse clinical outcomes including greater recurrence and lower rates of overall survival [12]. Breast cancer, particularly TNBC, is a heterogeneous disease, hence transcriptomic signatures have been developed to further stratify these cancers.…”
Section: Epidemiology and Classification Of Breast Cancermentioning
confidence: 99%
“…While TNBC accounts for only 15-20% of breast cancers, this intrinsic subtype is particularly aggressive, more likely to metastasize, and due in part to the lack of targeted therapies, results in worse clinical outcomes including greater recurrence and lower rates of overall survival [12]. Breast cancer, particularly TNBC, is a heterogeneous disease, hence transcriptomic signatures have been developed to further stratify these cancers.…”
Section: Epidemiology and Classification Of Breast Cancermentioning
confidence: 99%
“…Although preclinical studies have demonstrated promising results of cancer vaccines in TNBC, their clinical translation, safety, and efficacy have yet to be determined [ 11 , 20 , 21 ]. Thus, we aimed to systematically review the literature to provide a comprehensive update on the efficacy and safety of various vaccines against TNBC in the clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…TNBC accounts for 15-20% of all invasive breast cancer patients (4). 13.1 per 100,000 new TNBC cases among women were reported in 2021 around the world (5). 10.6% (22,375) of breast cancer cases were determined as TNBC in 2018 in Turkey (6).…”
Section: Introductionmentioning
confidence: 99%